Analysis of coach leadership style Pengprov of tarung derajat Aceh - Boihaqi, Boihaqi; Halim, Abdul (International Journal for Educational and Vocational Studies, 2021)
This study aims to knew the coachs leadership style Pengprov Tarung Derajat Aceh and the formation of a coaching leadership style. This research is an evaluation study with a descriptive approach. The research design including (1) determining the method or research design, (2) determining the population and research sample, (3) determining the research instrument, (4) collecting data, and (5) collecting analysis in accordance with the objectives and its nature. The instrument used to measure the coachs leadership style of the Pengprov Tarung Derajat Aceh is an instrument developed by the author with a grid of indicators that is authority, attitude, authoritarian coach style, democratic coach style and free coach style. The sample in this study amounted to 6 coachs people of Pengprov Tarung Derajat Aceh. The research method used is descriptive qualitative method. Data was collected using the Observation Format, Questionnaire and Interview Guidelines. The results of the data analysis showed that the leadership style of the coach of the Pengprov Tarung Derajat Aceh had a good leadership style in training, meaning that the leadership style of the Tarung Derajat Pengprov Aceh trainer used an authoritarian, democratic and free leadership style. Based on the data analysis, the writer concludes that the formation of the coachs leadership style Pengprov Tarung Derajat Aceh based on good regeneration means that the regeneration that has been carried out so far at the Pengprov Tarung Derajat Aceh is going well.